Principles of construction of departmental network of integral electirc communication u servicing of transport and road complex of Ukraine - Ільницький, Л. Я.; Петрашевський, О. Л.; Фузік, М. І. (Proceedings of National Aviation University (archive), 2000)
Considered are the main principles of construction of departmental network of integral electirc > communication servicing of transport and road complex of Ukraine